Active Control Experiments on a Smart Robotic Glass with End-Point Control for Parkinson's Patients - Ayana, Esra Kaya; Kilic, Mehmet; Yasar, Claudia F.; Engin, Seref Naci (WILEY, 2023)
This paper describes a robotic system that uses an actively controlled glass to help patients with tremors. End-point control is proposed for the upper part of a robotic device that becomes active in response to motion changes or vibrations of its holder. The device mechanisms, hardware, software, and sensory system are all integrated, presenting a novel robotic glass design. The control system consists of two degrees of freedom proportional-integral velocity regulators for direct current motors. These regulators are designed, implemented, and tuned to keep the robotic glass stable against changes in its position. In realizing direct current motor control, it is essential to take system constraints into consideration to develop regulators that can handle the nonlinear Coulomb friction and avoid operating in the saturation zone. This is crucial when designing, tuning, and implementing regulators for real-time applications. The computer simulations of the system, which involved developing and running all the control algorithms for real-time applications, are carried out in Matlab/Simulink. The proposed designs are validated by comparing system simulations to real-time physical experiments. The recorded results confirmed the outstanding performance of the proposed experimental platform mechanisms and the accurate control tracking, which provides fast and precise control responses to meet the high requirements of a fast end-point control application.
Keywords: ESSENTIAL TREMOR; SYSTEM; DESIGN; OBSERVERS; Engineering; Robotics